Pellet: fabricación y evaluación de pellets de especies forestales utilizadas en reforestación comercial en Costa Rica (Documento I) - Moya-Roque, Roger; Tenorio-M., Carolina (Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2014)
Pellets may be produced with different types of agriculture or forestry crops in Costa Rica. This work evaluated the energy, physical,and mechanical properties of pellets fabricated from 12types of agricultural and forestry crops (Ananas cumosos,Arundo donax,Coffea arabica,Cupressus lusitanica,empty fruit bunch and oil palm mesocarp fiber of the fruit of Elaeis guineensis,Gynerium sagittatum,Pennisetum purpureum,Phyllostachys aurea,Saccharum officinarum,Sorghum bicolor,and Tectona grandis),and similaritiesamongthese crops wereestablished by multivariate principal componentanalysis. High variation was found in the pellet properties. The energy evaluation revealed that C. lusitanica and P. aurea are the crops with the best qualities for fuel use because oftheir high calorific values (from 16807 kJ/kg and 19919 kJ/kg, respectively) and low ash content(1.03% and 3.39%, respectively). As for physical properties, most crops exhibitedvalues within the range noted by several authors and standards. All 12pellet crops displayed high durability (from 72.12% to 92.98%)and compression force(from 295.18 N to 691.86 N). Moreover, the evaluation of crop similarities allowed the determination of four group combinations. Within these groups, C. lusitanica, P. aurea, and G. sagittatum hadsimilar energy qualities and the best caloric characteristics.
Proyecto de Investigación. Código: 5401-1401-1024
Keywords: Fabricación; Evaluación; Especies forestales; Reforestación; Evaluation; Forest species; Reforestation; Manufacturing; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area technology::Forest engineering